Influence of Silver Nanoparticles on Optical Properties for (PS-PMMA) Blend - Saba Salim Nemah (Journal of Global Pharma Technology, 2016)
The optical properties of poly (methyl metha acrylate) (PMMA) with polystyrene (PS) blend films doped with silver nanoparticles were studied. The blend films were prepared using solution casting technique different weight ratio (0, 2.0, 4.0, and 6.0 wt %) of the Ag nanoparticles, the optical properties of the prepared films were investigated. The optical absorption spectra of these films in the wavelength range from (320-1100 nm) were measured to investigate the influence of Ag nanoparticles on the optical properties of (PS-PMMA) blend. The results showed that energy gap of the blend films decreases with increasing Ag nanoparticles weight ratio. The absorbance, absorption coefficient, extinction coefficient, refractive index, parts dielectric constant (real and imaginary) of the prepared (PS- PMMA) blend films were found to be increased with increasing the weight ratio of Ag nanoparticles.Keywords: Nanoparticls, Optical properties, (ps-pmma) polymer.